REDD+ en Latinoamérica: el caso de Perú - Ladd, Brenton (2013)
The question of how developing countries like Peru can participate effectively in the REDD+ (reducing emissions from deforestation and forest degradation) policy initiative of the United Nations has been the focus of considerable debate recently. The aim of this study was to detect the main challenges associated with monitoring deforestation and forest degradation and also to analyze the policy challenges associated with implementing REDD in Peru. To participate effectively in this process, it is essential that the Peruvian national government formulates a national response since it is unlikely that provincial agencies managing natural resources will be able to develop the necessary expertise to carry out effective monitoring, reporting and verification, and because the underlying factors driving deforestation will require a large investment and a coordinated response at the country level.